Bottom-Up Approach of Teacher's Best Practice to Avoid Student's Perplexity in Listening - Rina Herlina (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
This best practice aims to find out teachers’ practice on the bottom-up approach in teaching listening to EFL students at the higher education level, to find out students’ perplexity on listening, and to find out students’ responses on the bottom-up approach in teaching listening. The bottom-up approach has been practiced due to students’ perplexity in figuring out some linguistic features such as short and long vowels, word linking, diverse English accents, diction, and many others which are not available in EFL students’ native language. Thus, the students frequently have perplexity in those aspects. This perplexity occurs due to linguistic features in English are being far different from the ones in the Indonesian language. This qualitative research employed one English teacher who is particularly in charge of teaching listening and ten freshman students. The finding revealed that a bottom-up approach to the freshman classes is given until they get used to it so that they can get well-prepared to have a top-down approach to listening and students’ responses indicate that they no longer have perplexity about listening to English native speakers. The conclusion showed that before teaching listening with a top-down approach, a bottom-up approach would be initially practiced. The Bottom-Up approach has been applied to prevent EFL students from perplexity in listening and they will be ready to face other techniques such as listening for gist, specific information, and detail. Keywords: bottom-up approach, teaching listening, EFL students’ perplexity